Continuous thermosalinograph oceanography along RV MARIA S. MERIAN cruise track MSM132 - Michael Schlundt; Christian Berndt; Andrea Greipel (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems. Usually, the systems are changed after 6 hours. While temperature is taken at the water inlet in about 6.5 m depth, salinity is estimated within the interior measurement container from conductivity and interior temperature. No temperature calibration was performed. Salinity was calibrated with discrete water samples taken close to the seawater inlet. For details to all processing steps see Data Processing Report.